2015
DOI: 10.1039/c4md00306c
|View full text |Cite
|
Sign up to set email alerts
|

3-Propionyl-thiazolidine-4-carboxylic acid ethyl esters: a family of antiproliferative thiazolidines

Abstract: Modification at the 2-position of the apoptosis-inducing compound ALC 67 enables tuning of its physicochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…[38][39][40] We also presented the anticarcinogenic property of an acetylenic thiazolidine, namely, the ALC67 molecule in a previous study, 29 and showed recently that 3-propionyl-thiazolidine-4-carboxylic acid ethyl esters can be classified as a family of antiproliferative compounds. 41 Given the potency of this core structure, we wanted to investigate the mutagenicity and the genotoxicity of these acetylenic thiazolidine, choosing ALC67 molecule as the reference molecule.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] We also presented the anticarcinogenic property of an acetylenic thiazolidine, namely, the ALC67 molecule in a previous study, 29 and showed recently that 3-propionyl-thiazolidine-4-carboxylic acid ethyl esters can be classified as a family of antiproliferative compounds. 41 Given the potency of this core structure, we wanted to investigate the mutagenicity and the genotoxicity of these acetylenic thiazolidine, choosing ALC67 molecule as the reference molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The 1,3-thiazolidin-4-one derivatives are very important core structures of many heterocyclic compounds. Thiazolidinone and its analogues have outstanding biological activity, they are reported as antiinflammatory [15], antimicrobial [16], antidiabetic [17], anticancer [18], antioxidants [19]. On the other hand, thiazole is a well-known heterocyclic aromatic compound containing sulphur and nitrogen atoms at positions 1 and 3 of its five-member ring, respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous heterocyclic compounds containing nitrogen, sulfur, and oxygen heteroatoms have attracted the attention of chemists over the years because of their biological properties. In particular, the thiazolidin-4-ones, a privileged pharmacophore possesses an array of biological activities including anti-inflammatory [ 9 ], antimicrobial [ 10 ], antibiofilm [ 11 ], antiparasitic [ 12 ], anticancer [ 13 ], anti-viral [ 14 ], antidiabetic [ 15 ], antiarthritic [ 16 ], FSH agonist [ 17 ], JNK stimulating phosphatase-1 (JSP-1) [ 18 ], CNS-penetrant [ 19 ], CDK1/Cyclin B inhibition [ 20 ], COX-2 inhibitor [ 21 ] and hypoglycemia [ 22 ] properties. In the last few years, Kucukguzel et al developed substituted 4-thiazolidinones and among them compounds 1 and 4 exhibited excellent antitubercular activity with 90% and 98% inhibitions at 6.25 µg/mL, respectively [ 23 ].…”
Section: Introductionmentioning
confidence: 99%